Spectrum of acute kidney injury in patients of tropical acute febrile illness in a tertiary hospital - Badge, Rohit P.; Babu, V. Suresh; Rathore, Vinay (International Journal of Research in Medical Sciences, 2023)
Background: Tropical acute febrile illnesses (TAFI) such as malaria, typhoid, leptospirosis, dengue are major causes of AKI in the tropics. The spectrum of AKI due to TAFI in developing countries like India is still underestimated. Hence, we conducted a study to know the spectrum of AKI in patients of TAFI. Methods: The prospective study was conducted in Yashoda hospital, Secunderabad a tertiary care hospital in India from April 2019 to March 2020. AKI was defined as per KDIGO. The clinical history, physical examination and laboratory investigations were recorded in a standard proforma. Results: Hundred patients suffering from TAFI were admitted during the study period. Mean age of the study population was 43.12±14.33 years. Twenty-six (60.5%) were males. Most common presenting feature was fever (100%), chills (81.4%) and vomiting (67.4%). The most common cause of TAFI was dengue (n=49, 49%), leptospirosis (n=20, 20%), followed by malaria (n=10, 10%), scrub typhus (n=10, 10%) and undifferentiated fever (n=6, 6%). 43 patients (43%) had AKI as per KDIGO definition. 23 patients (53.5%) had stage 1, 11 (25.6%) had stage 2 and 9 (20.9%) had stage 3 AKI. RRT was required in 16.3% of patients. Dengue and leptospirosis were the most common causes for requirement of RRT. SLED was the most common modality of dialysis. Mortality was observed in 6.98% patients and Dengue was the most common cause of mortality. Conclusions: AKI is common in tropical acute febrile illness. However, RRT was required only in 16.3% and mortality was observed in 6.98% patients.